2021
DOI: 10.3390/app112412013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Periodontal Pain Using Two Different Orthodontic Techniques, Fixed Multibrackets and Removable Aligners: A Longitudinal Clinical Study with Monthly Follow-Ups for 12 Months

Abstract: The aim of this study was to evaluate the perception of periodontal pain in patients treated with either fixed multibrackets or removable alignment systems with a monthly follow-up over a period of twelve months. Materials and Methods: This longitudinal clinical study comprised a sample of 140 patients (72 women; 68 men) divided into two groups of 70 patients each: the bracket group (BG) with conventional fixed brackets using the MBT technique with a 0.022″ slot and the Invisalign group (IG) with aligners (Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A systematic review found that patients treated with aligners reported lower levels of pain compared to those treated with fixed appliances during the first days of treatment, but there was no difference throughout treatment. 39 These results have been confirmed by clinical studies published subsequently, 40 including a prospective clinical study. 41 It is common that during orthodontic treatment patients experience some discomfort during the adaptation process, because the devices cause pain or even interfere with tongue movements, limiting the space for tongue accommodation and therefore the patient's speech.…”
Section: Can Orthodontic Treatment With Aligners Im-pact On the Oral ...mentioning
confidence: 64%
“…A systematic review found that patients treated with aligners reported lower levels of pain compared to those treated with fixed appliances during the first days of treatment, but there was no difference throughout treatment. 39 These results have been confirmed by clinical studies published subsequently, 40 including a prospective clinical study. 41 It is common that during orthodontic treatment patients experience some discomfort during the adaptation process, because the devices cause pain or even interfere with tongue movements, limiting the space for tongue accommodation and therefore the patient's speech.…”
Section: Can Orthodontic Treatment With Aligners Im-pact On the Oral ...mentioning
confidence: 64%